2021
DOI: 10.1186/s12950-021-00287-3
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine hydrochloride inhibits hepatocyte apoptosis and inflammation by activating the lncRNA TUG1/miR-194/SIRT1 signaling pathway

Abstract: Background Liver injury seriously threatens the health of people. Meanwhile, dexmedetomidine hydrochloride (DEX) can protect against liver injury. However, the mechanism by which Dex mediates the progression of liver injury remains unclear. Thus, this study aimed to investigate the function of DEX in oxygen and glucose deprivation (OGD)-treated hepatocytes and its underlying mechanism. Methods In order to investigate the function of DEX in liver in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Previous studies24 demonstrated that miR194 was regulated by taurine‐upregulated gene 1 ( TUG1 ), a long noncoding RNA, which is upregulated by taurine. TUG1 induced an epigenetic regulator that enhances zeste homolog 2–associated promoter methylation and can directly bind to and act as a biological sponge to reduce miR194 expression 25.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies24 demonstrated that miR194 was regulated by taurine‐upregulated gene 1 ( TUG1 ), a long noncoding RNA, which is upregulated by taurine. TUG1 induced an epigenetic regulator that enhances zeste homolog 2–associated promoter methylation and can directly bind to and act as a biological sponge to reduce miR194 expression 25.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, increasing evidence has suggested the regulatory effect of DEX toward the lncRNA, such as SHNG16, 35 SNHG14, 36 TUG1, 37 and PACER 38 . Our work demonstrated that DEX could reduce the expression of MALAT1 in a dose‐dependent manner, while the in vivo models also presented the ability of DEX to reduce the expression of MALAT1 in the xenograft tumors, highlighting the important role of DEX in EC via mediating the expression of MALAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies indicate that lncRNAs participate in various biological processes involved in HIRI development. A few studies revealed that some lncRNAs, including TUG1[ 132 ], NEAT1[ 133 ], MALAT1[ 134 ] and Hnf4αos[ 135 ], could modulate the processes of apoptosis and inflammatory response. Other lncRNAs, such as MEG3[ 136 ], Gm4419[ 137 ], CCAT1[ 138 ] and AK054386[ 139 ] were verified to regulate apoptosis, whereas AK139328 was only found to regulate the inflammatory response[ 130 ].…”
Section: Lncrnasmentioning
confidence: 99%